RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF ARTICULATE STORYLINE PADA MATA PELAJARAN IPS JENIS-JENIS PEKERJAAN DI SEKOLAH DASAR - Devita Syafitriyani; Komariah Komariah; Yona Wahyuningsih (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
This research is motivated by optimizing the concept of types of work including jobs based on geographic location in social studies learning for grade IV in elementary schools, so that interactive learning media articulated storylines for types of work were developed. This study aims to produce products from the design of interactive learning media articulate storyline, describe the feasibility of the media from the validation results of experts including material experts, linguists and media experts, as well as user responses, namely teachers and students, to the use of interactive learning media. By using articulate storyline interactive learning media, it is hoped that the media can help students at different levels of abstraction because of the images in the multimedia. This study uses the Design and Development method using the ADDIE model development (Analyze, Design, Development, Implementation, and Evaluation). Participants in this study involved material experts, linguists and media experts to provide an assessment of this interactive learning media. Data collection techniques carried out on this media used unstructured questionnaires and interviews. The results of this study indicate that the articulate storyline interactive learning media gets a very feasible category as a medium to be used in learning, especially social studies. Based on the results of limited product trials, this interactive learning media obtained a very feasible category from material experts with aspects of material, display, program, learning and language. The responses from users, namely teachers and fourth grade students at SDN Bedahan 02 gave an assessment in the